The Effectiveness of Gym Ball and Ambon Banana Consumption Against Menstrual Pain Reduction in Teenagers - Hidayah, Nur; Fatmawati, Rizka (Journal of Maternal and Child Health, 2022)
Background: There are many ways to eliminate or reduce pain, both pharmacologically. Non-pharmacological pain management is safer to use because it does not cause side effects like drugs, because non-pharmacological therapy uses physiological processes. Research Objectives The purpose of this study was to analyze the effectiveness of the Gym Ball and bananas on the reduction of menstrual pain in adolescents. Subjects and Method: A quasi research without a control group was conducted at SMP N 23 Surakarta, Central Java, from April to September 2019. A sample of 46 students was selected by accidental sampling. The dependent variable is menstrual pain. The independent variable is gymball and the provision of ambon bananas. Pain scale was measured by a verbal rating scale questionnaire. Data were analyzed by paired t-test. Results: Pain scores after treatment (Mean= 0.76; SD= 0.60) were lower than before treatment (Mean= 1.93; SD= 0.39), and were statistically significant (p= 0.001). Conclusion: There is an effect of gym ball and banana consumption to reduce menstrual pain.